2021
DOI: 10.1002/ajmg.a.62347
|View full text |Cite
|
Sign up to set email alerts
|

TSPEAR variants are primarily associated with ectodermal dysplasia and tooth agenesis but not hearing loss: A novel cohort study

Abstract: Biallelic loss-of-function variants in the thrombospondin-type laminin G domain and epilepsy-associated repeats (TSPEAR) gene have recently been associated with ectodermal dysplasia and hearing loss. The first reports describing a TSPEAR disease association identified this gene is a cause of nonsyndromic hearing loss, but subsequent reports involving additional affected families have questioned this evidence and suggested a stronger association with ectodermal dysplasia. To clarify genotype-phenotype associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
(125 reference statements)
0
15
0
1
Order By: Relevance
“…Phenotypes associated with biallelic TSPEAR variants can be categorized into: (1) ED with or without TA (57.9%); (2) TA without other ectodermal features (e.g., isolated TA or TA with other non-ED-related features) (21.1%); (3) SNHL without ED features (18.4%); and (4) SNHL with ED, which was reported in only one patient (2.6%). Only four previously reported patients had ED without TA; however, they had conical-shaped teeth, which does not fulfill the criteria of TA; still, it suggests the involvement of teeth [ 24 ]. Clinical presentation of dysmorphic facial features showed statistically high significant dependence ( p = 0.0001) on ethnic origin.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phenotypes associated with biallelic TSPEAR variants can be categorized into: (1) ED with or without TA (57.9%); (2) TA without other ectodermal features (e.g., isolated TA or TA with other non-ED-related features) (21.1%); (3) SNHL without ED features (18.4%); and (4) SNHL with ED, which was reported in only one patient (2.6%). Only four previously reported patients had ED without TA; however, they had conical-shaped teeth, which does not fulfill the criteria of TA; still, it suggests the involvement of teeth [ 24 ]. Clinical presentation of dysmorphic facial features showed statistically high significant dependence ( p = 0.0001) on ethnic origin.…”
Section: Resultsmentioning
confidence: 99%
“…We compared clinical phenotypes and dysmorphic facial features of our studied cohort of patients to previously published cases that were similarly identified to harbor biallelic TSPEAR disease causing variants [ 24 , 25 , 27 , 28 , 29 , 55 , 56 ]. Patients were grouped according to their reported ethnicities into: North African, Middle Eastern, European and others.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of ectodermal dysplasia and the molecular basis of many of these disorders are still unknown [ 3 ]. Recent reports have shown that loss-of-function variants within the thrombospondin-type laminin G domain and epilepsy-associated repeats (TSPEAR) gene have recently been related to ectodermal dysplasia [ 4 ]. TSPEAR mutations or down-regulation resulted in altered expression of genes known to be regulated by the NOTCH signaling pathway and to be involved in murine hair and tooth development.…”
Section: Introductionmentioning
confidence: 99%